Kondisi Psikologis Siswa SMP Pasca Gempa Bumi di Kecamatan Meureudu Pidie Jaya - Susiyanti Misfitri; Syaiful Bahri; Abu Bakar (JIMBK: Jurnal Ilmiah Mahasiswa Bimbingan & Konseling, 2018)
This study entitled "Psychological Condition of Junior High School Students After Earthquake in Meureudu, Pidie Jaya" The purpose of research to know the psychological condition of students after earthquake. The approach used is descriptive quantitative research. The study sites were SMPN 1 and 2 Meureudu Pidie Jaya, with a population of 654 students. Sampling using random sampling technique to determine the number of samples by using slovin formula that is as many as 248 students. Data collection using an instrument. Data analysis uses quantitative descriptive. The results showed psychological condition. Judging from the number of respondents' answers on every aspect of psychological condition, or category mostly (78.6%), the category is very disturbed or called very little (13.6%) and uninterrupted or a small part (7, 9%). The cognition aspect of the category or the like (65.5%), is very disturbed or called a small part (23.6%) and is not disturbed or is called very little (11.1%). The emotional aspect of the category or most of which is (63.2%), very disturbed or very little (18.9%) and uninterrupted or slightly at all 17.8%). The behavioral aspect of the category or most (65.6%), is very disturbed or called a small part (28,9) and is not disturbed or very little (5.4%). The social aspect on the category or (42,4%), is very disturbed or mostly (30,4%) and not disturbed or (28,2%) Generally psychological condition of student after earthquake in category or mostly 68,9 %), the category is very disturbed or very little (18.9%), and the category is not compromised or slightly (12.1%).